2009
DOI: 10.1299/jsdd.3.932
|View full text |Cite
|
Sign up to set email alerts
|

Chaos-Entropy Analysis and Acquisition of Human Operator's Skill Using a Fuzzy Controller: Identification of Individuality during Stabilizing Control of an Inverted Pendulum

Abstract: In order to stabilize the inherent unstable system like the inverted pendulum on a cart, severe judgment of situation is required. Accordingly, it can be expected that human operators exhibit complex behavior intermittently. This paper investigated the identification of the individual difference of human operator's behavior from time series data by using fuzzy inference and acquired individual skill of human operator. It also investigated the chaotic behavior of human operator and the formation of a complex sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The behavior during stabilizing control of an inverted pendulum by a human operator exhibits a random-like or limit-cycle like fluctuation, and the stabilizing control by the human operator is robust against the disturbance. This may be because the limit-cycle-like fluctuation with a digital computer control, which means lineally unstable, is more robust against the disturbance than the lineally stable fluctuation investigated in previous experiments (6), (14) . Furthermore the limit cycle is very stable in the sense of nonlinearity, which means it is very strong against the disturbance, because the trajectories near the limit cycle spiral onto it from its inside and outside (15)- (17) .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The behavior during stabilizing control of an inverted pendulum by a human operator exhibits a random-like or limit-cycle like fluctuation, and the stabilizing control by the human operator is robust against the disturbance. This may be because the limit-cycle-like fluctuation with a digital computer control, which means lineally unstable, is more robust against the disturbance than the lineally stable fluctuation investigated in previous experiments (6), (14) . Furthermore the limit cycle is very stable in the sense of nonlinearity, which means it is very strong against the disturbance, because the trajectories near the limit cycle spiral onto it from its inside and outside (15)- (17) .…”
Section: Introductionmentioning
confidence: 77%
“…Accordingly, it can be expected that the human operators exhibit a complex behavior intermittently. In the author's previous papers (6)- (14) , it was found that there are various nonlinear features in the stabilizing behavior of a human operator. In this study, the definition of nonlinear stability means that an inverted pendulum does not fall for 60 consecutive seconds.…”
Section: Introductionmentioning
confidence: 99%
“…The term "relax" in sports refers to a freeing of the degrees of freedom (DOF). In order to achieve a new motion, it is considered necessary to initially stiffen the body or to freeze the number of degrees of freedom (1) - (3) . Figure 1 shows a series of photographs taken by the authors showing "the movement of a cake craftsman" presented by Yoshinori Kono, where Fig.…”
Section: Introductionmentioning
confidence: 99%
“…6, 2010 were trained so that they were skilled to a certain extent in stabilizing the pendulum, and the data obtained in 10 successive trials per person were used for analysis. The angle that the pendulum makes with the vertical axis and the displacement of the cart were measured, and the derivatives and the force that moves the cart can be derived based on these quantities (2) (3) .…”
mentioning
confidence: 99%
See 1 more Smart Citation